Prevalence and distribution of Borrelia and Babesia species in ticks feeding on dogs in the U.K. Issue 1 (28th August 2017) - ABDULLAH, S.; HELPS, C.; TASKER, S.; NEWBURY, H.; WALL, R.
Abstract: Ticks were collected during March–July 2015 from dogs by veterinarians throughout the U.K. and used to estimate current prevalences and distributions of pathogens. DNA was extracted from 4750 ticks and subjected to polymerase chain reaction and sequence analysis to identify Borrelia burgdorferi sensu lato (Spirochaetales: Spirochaetaceae) and Babesia (Piroplasmida: Babesiidae) species. Of 4737 ticks [predominantly Ixodes ricinus Linneaus (Ixodida: Ixodidae)], B. burgdorferi s.l . was detected in 94 (2.0%). Four Borrelia genospecies were identified: Borrelia garinii (41.5%); Borrelia afzelli (31.9%); Borrelia burgdorferi sensu stricto (25.5%), and Borrelia spielmanii (1.1%). One Rhipicephalus sanguineus Latreille (Ixodida: Ixodidae), collected from a dog with a history of travel outside the U.K., was positive for B. garinii . Seventy ticks (1.5%) were positive for Babesia spp. Of these, 84.3% were positive for Babesia venatorum, 10.0% for Babesia vulpes sp. nov., 2.9% for Babesia divergens/Babesia capreoli and 1.4% for Babesia microti . One isolate of Babesia canis was detected in a Dermacentor reticulatus (Ixodida: Ixodidae) tick collected from a dog that had recently travelled to France. Prevalences of B. burgdorferi s.l . and Babesia spp. did not differ significantly between different regions of the U.K. The results map the widespread distribution of B. burgdorferi s.l. and Babesia spp. in ticks in the U.K. and highlight the potential for the introduction and establishment of exotic ticks and tick‐borne pathogens. Abstract : In this study, ticks were collected from dogs by veterinarians participating in a U.K.‐wide tick surveillance programme. The ticks were subjected to polymerase chain reaction and sequence analysis for detection of Borrelia burgdorferi s.l . and Babesia spp. pathogens, the distributions of which were mapped. DNA of B. burgdorferi s.l . and Babesia spp. was detected in 2.0% and 1.5% of the ticks analysed, respectively. The results map a widespread distribution of the two pathogens in the U.K.